Islamic insurance in the global economy - Galal, Fatima A.; Kabbashi, Nassereldeen Ahmed (International Journal of Business and Management Invention (IJBMI), 2017)
Islamic insurance industry is experiencing a period of rapid growth in terms of its net contributions and profit, however, at the same time, the development of this industry is still faced with tough obstacles and constraints due to the Shar'iah issues in some certain aspects. Islamic insurance operations need to be fine-tuned to meet the Islamic direction and the needs of Muslims. There are many different operational models with various Islamic jurisdictions trying to meet the needs of Muslims in general as regard Islamic insurance in the global Islamic economy. The two challenging issues that are studied are the ownership of the Islamic insurance risk fund and the surplus distribution accumulated from the risk fund. The findings reviewed that insurance principles contribute substantially to Islamic insurance operation (β = 0.405) justification in terms of Islamic features and operator fees (β =0.925) and (β =0.255) respectively.